Multicenter Evaluation Of Coronary Dual-Source CT angiography in patients with intermediate Risk of Coronary Artery Stenoses (MEDIC): study design and rationale - Hausleiter, Jörg; Abbara, Suhny; Hoffmann, Udo; Becker, Christoph; Ovrehus, Kristian; Ropers, Dieter; Bathina, Ravi; Berman, Dan; Anders, Katharina; Uder, Michael; Meave, Aloha; Alexánderson, Erick; et al. (Journal of Cardiovascular Computed Tomography, 2014)
The diagnostic performance of multidetector row CT to detect coronary artery stenosis has been evaluated in numerous single-center studies, with only limited data from large cohorts with low-to-intermediate likelihood of coronary disease and in multicenter trials. The Multicenter Evaluation of Coronary Dual-Source CT Angiography in Patients with Intermediate Risk of Coronary Artery Stenoses (MEDIC) trial determines the accuracy of dual-source CT (DSCT) to identify persons with at least 1 coronary artery stenosis among patients with low-to-intermediate pretest likelihood of disease.The MEDIC trial was designed as a prospective, multicenter, international trial to evaluate the diagnostic performance of DSCT for the detection of coronary artery stenosis compared with invasive coronary angiography. The study includes 8 sites in Germany, India, Mexico, the United States, and Denmark. The study population comprises patients referred for a diagnostic coronary angiogram because of suspected coronary artery disease with an intermediate pretest likelihood as determined by sex, age, and symptoms. All evaluations are performed by blinded core laboratory readers.The primary outcome of the MEDIC trial is the accuracy of DSCT to identify the presence of coronary artery stenoses with a luminal diameter narrowing of 50% or more on a per-vessel basis. Secondary outcome parameters include per-patient and per-segment diagnostic accuracy for 50% stenoses and accuracy to identify stenoses of 70% or more. Furthermore, secondary outcome parameters include the influence of heart rate, Agatston score, body weight, body mass index, image quality, and diagnostic confidence on the accuracy to detect coronary artery stenoses >50% on a per-vessel basis.The results of the MEDIC trial will assess the clinical utility of coronary CT angiography in the evaluation of patients with intermediate pretest likelihood of coronary artery disease.
EVALuna2:14371